A study on the proxemics of the social hall of the University of the Philippines International Center - Kuo, Fan-sheng.; Mayo, Adelaida V.; University of the Philippines International Center (2007., 2007)
This study sought to find out the similarities and perceptions among student-residents toward space use of the University of the Philippines International Center (UPIC) social hall. The study determined the respondents' demographical characteristics, namely, nationality, gender, length of stay, and religious affiliation, and established the frequency of their use of the UPIC social hall. Using the descriptive - comparative research design, data was obtained through the following tools: pictures as visual instruments, floor plans of UPIC and the survey questionnaire. Results showed the following: 1) Foreign student-residents preferred socialization more compared to Filipino student-resident; 2) the longer the residents' stay in UPIC, the lesser he/she used the social hall to interact with the other student residents; 3) male residents use the social hall space (everyday to once a week) more than the female residents; 4) the presence of bright lighting and cool colors is basically preferred by student resident; 5) there were more Filipino and Japanese student residents in UPIC compared with the other foreign student-residents; and 6) most of the student residents' main purpose of utilizing the social hall was to watch television. Applying the theory of Proxemics as a framework for analyzing the results of the study, it was established that the student residents- preferred a furniture layout in the social hall that promotes and encourages private group interactions among residents. Physical enhancement of the social hall was likewise preferred by the student-residents in terms of changing the existing color schemes into brighter and more cheerful colors, improvement of its ventilation, and applying better lighting. While religious affiliation bore no significant relationship with regards to the residents preferred design elements, the different cultural orientations of the residents should be taken into consideration in designing the UPIC social hall. A suitably designed converging area should be made available to multi-cultural student-residents who may have differing interpretations of space and privacy but are united in their need to establish social relationships as a means of getting by while studying in a foreign country.
Thesis (M. Interior Design)--University of the Philippines Diliman.
Keywords: Dormitories -- Decoration. -- Philippines -- Quezon City